Effects of acute versus repeated cocaine exposure on the expression of endocannabinoid signaling-related proteins in the mouse cerebellum - Palomino, Ana; Pavon, Francisco Javier; Blanco Calvo, Eduardo; Serrano, Antonia; Arrabal, Sergio; Rivera, Patricia; Vargas, Antonio; Bilbao, Ainhoa; Rubio, Leticia; Rodriguez de Fonseca, Fernando; Suarez, Juan (Frontiers in Integrative Neuroscience, 2014)
Growing awareness of cerebellar involvement in addiction is based on the cerebellum’s intermediary position between motor and reward, potentially acting as an interface between motivational and cognitive functions. Here, we examined the impact of acute and repeated cocaine exposure on the two main signaling systems in the mouse cerebellum: the endocannabinoid (eCB) and glutamate systems. To this end, we investigated whether eCB signaling-related gene and protein expression (CB1 receptors and enzymes that produce (DAGLα/β and NAPE-PLD) and degrade (MAGL and FAAH) eCB) were altered. In addition, we analyzed the gene expression of relevant components of the glutamate signaling system (glutamate synthesizing enzymes LGA and KGA, mGluR3/5 metabotropic receptors, and NR1/2A/2B/2C-NMDA and GluR1/2/3/4-AMPA ionotropic receptor subunits) and the gene expression of tyrosine hydroxylase (TH), the rate-limiting enzyme in catecholamine biosynthesis, because noradrenergic terminals innervate the cerebellar cortex. Results indicated that acute cocaine exposure decreased DAGLα expression, suggesting a down-regulation of 2-AG production, as well as gene expression of TH, KGA, mGluR3 and all ionotropic receptor subunits analyzed in the cerebellum. The acquisition of conditioned locomotion and sensitization after repeated cocaine exposure were associated with an increased NAPE-PLD/FAAH ratio, suggesting enhanced anandamide production, and a decreased DAGLβ/MAGL ratio, suggesting decreased 2-AG generation. Repeated cocaine also increased LGA gene expression but had no effect on glutamate receptors. These findings indicate that acute cocaine modulates the expression of the eCB and glutamate systems. Repeated cocaine results in normalization of glutamate receptor expression, although sustained changes in eCB is observed. We suggest that cocaine-induced alterations to cerebellar eCB should be considered when analyzing the adaptations imposed by psychostimulants that lead to addiction.